A practical approach to river water quality modeling - Zainudin, Zaki; Mohamed, Maketab; Tengku Yahya, Tengku Fazli (IIUM Press, 2011)
Water Quality Modeling (WQM) is an integral part of watershed management in Malaysia as well as many other countries in the world. They are employed for various purposes, such as impact assessment due to development, river rehabilitation studies as well as non-point source pollution characterization. There are various types of water quality models available commercially and as well as freeware; however, QUAL2E and QUAL2K under the purview of the United States Environmental Protection Agency (USEPA) are two of the most popular freeware models available. Brown and Barnwell developed QUAL2E, in the 1980s, using a FORTRAN based programming language. However, due to rapid advancements in computer technology and operating platform, QUAL2E is unable to converge in current popular systems such as Windows XP and Vista, thus the model required a DOS based windows OS such as Windows ME and Windows 98. Albeit being the case, the model stills remains popular due to the simplicity of the user interface and relatively straightforward data requirement. The utilization of virtual emulators facilitate a workaround to this problem, and thus, as benefit, QUAL2E can then be utilized to run in any desktop environment, including non-native Windows platforms such as Linux. The procedures for the workaround are discussed extensively in this book. On the other hand, renowned environmental professor and numerical specialist, Steven Chapra of Tufts University and his team, developed a modernized version of QUAL2E, dubbed QUAL2K, with of course, certain upgrades and more stringent data requirements. The model is available for download from the US EPA website and is regularly updated by its authors. This book does not aim to discuss the underlying mathematical formulations of QUAL2E nor QUAL2K, as the respective developers have developed sufficient user manuals, which deal with these aspects. Instead, the focus is on the hand-on utilization of QUAL2E/2K, including a step-by-step guide, addressing practical issues related to model development, particularly in terms of data availability and analysis. It is hoped that the reader will be able to appreciate and correlate the various abstract principles involved behind these formulations with the actual physico-chemical and biological processes that transpire within the water column.